Devoluciones en mercadería y su incidencia en las ventas de representaciones y servicios en general San Francisco S.A.C., 2018 - Sánchez Máchica, Carla Pamela (2020)
The general objective of this research work was to determine how merchandise returns affect sales of Representations and Services in General San Francisco SAC, 2018. For this reason, the research problem was formulated: How do returns in merchandise affect sales of Representations and Services in General San Francisco SAC, 2018? This thesis work presented a non-experimental, transactional or cross-sectional research design, a descriptive and correlational type of research, the sampling used was convenience sampling , where the sample was chosen, which consisted of the records of sales and returns of the company's merchandise. For data collection, the technique of documentary analysis, direct observation and internet browsing was used; Statistical formulas such as Pearson's correlation were used to establish the relationship of the variables, later computer tools were applied on the MS Excel platform for tabulation and preparation of tables and graphs. Subsequently, it was concluded: it was determined that merchandise returns have a direct impact on the sales of Representaciones y Servicios en General San Francisco S.A.C, 2018, having an annual average loss of 4.8%, expressed in national currency at 130,583. In addition, the existing relationship between merchandise returns and the incidence in sales of Representaciones y Servicios en General San Francisco S.A.C, 2018 was determined, being 0.967 points, classified on the Pearson scale as a very strong positive correlation.